THE EXPERIMENTATION OF MIND MAPPING-BASED NUMBER HEAD TOGETHER (MMNHT) AND MIND MAPPING-BASED THINK PAIR SHARE (MMTPS) IN THE TOPIC OF QUADRATIC FUNCTION - Yosita Eka Yuliana; Budiyono Budiyono; Isnandar Slamet (Proceedings Education and Language International Conference, 2017)
This article is motivated by my previous research. Based on the fact, it can be said that this kind of innovation in model learning is very potential to be used in schools. This study is quasi-experimental research aimed to identify differences in the effect of each model of learning on students’ learning achievement. The study used subjects from the whole population of the Tenth Grader sof high schools in Magetan in the academic year of 2016/2017. Those samples were chosen through stratified cluster random sampling. The data in the study were collected using test, questionnaire, and documentation, and then, were analyzed using Lilliefors, Barlett, and one way ANOVA (pre-requisite tests) and one way ANOVA (Hypotheses test). Based on the hypotheses test result that mathematics learning achievement of the tenth graders of public high school in Magetan who were treated with Mind Mapping-based NHT have better achievement than Mind Mapping-based TPS or Mind Mapping-based direct and Mind Mapping-based TPS have better achievement than Mind Mapping-based direct. Keywords: Number Head Together (NHT), Think Pair Share (TPS) Mind Mapping, Quadratic Function.